A geophysical survey in the archaeological site of Archontiko, Yannitsa - SAVVAIDIS, A.; TSOKAS, G.; TSOURLOS, P.; VARGEMEZIS, G.; CHRYSOSTOMOU, A.; CRYSOSTOMOU, P. (Bulletin of the Geological Society of Greece, 2001)
The ancient settlement of Archontiko is 4.5 km NW of ancient Pella in North Greece (Figure 1). The findings showed that the area was first occupied by the end of the Iron Age, i.e. 650-550 B.C. Also, showed that the topographic table of Archontiko was a major settlement of the Yannitsa province due to its concessive position by the main roads of Macedonia (Chrysostomou A. and Chrysostomou P., 1993). At the upper layers of the ruins, findings of the Roman and Byzantine times were also unearthed. The geophysical methods have been used in order to detect and map antiquities in various sites in Greece (e.g., Tsokas et al., 1994; 1995; Sawaidis et al., 1999). The resistivity mapping employing the twin probe array, the total magnetic field variations, the airborne photos and the Ground Probing Radar are the most popular methods in this respect. However, almost all geophysical methods can be used to tackle specific problems. From 1992 till 1994, many geophysical surveys were carried out in the area of Archontiko to collect mainly magnetic data. Resistivity measurements were also conducted in a small part of the area. The data presented in this study cover the northern side of the topographic table of Archontiko and they were collected during two campaigns during the summer of the years 1992 and 1993 (Figure 2).